European standards for ensuring the principle of the prosecutor's office - Boiko, Petro (Actual problems of law (Aktual'ni problemi pravoznavstva), 2023)
The article discusses the basic European standards for ensuring the principle of independence of the prosecutor's office.It has been established that increased attention to existing international standards in the field of human rights, which accumulate the most advanced legal concepts that determine the legal status of a person, is a natural reflection of the modern trend in the direction of strengthening guarantees of the independence of prosecutor's office workers. After all, the mechanism of building procedural legal relations depends on the attitude of the state towards the official, his dignity, interests, and rights. Based on the provisions of international legislation, in many countries, there is a surge of reform activity, which is based both on the accounting of international law and on the desire to create something new instead of international legal regulation.It is substantiated that the integration of the Ukrainian prosecutor's office into the judicial system will be a fundamental fundamental step on the way to its reform, which will make it possible to ensure the impartiality, independence, and depoliticization of its activities and will correspond to the established modern trends of the prosecutor's office in the democratic role of the state. Not only such European democracies as Belgium, Spain, Italy, the Netherlands, Greece, Portugal, France, and Finland, but also Azerbaijan, Armenia, Georgia, Kazakhstan, Moldova, Russia, Latvia, Lithuania, Bulgaria, and Romania.The author concludes that an essential task for our country is not only the implementation of the main European standards and principles but also the development of specific mechanisms necessary for reforming the prosecutor's office of Ukraine. It is necessary to determine at the constitutional level that the prosecutor's office is an independent body in the judicial system, to optimize its function, to improve the guarantees of ensuring the independence of prosecutors, the procedure for their appointment, the grounds and procedure for the dismissal of the Prosecutor General, to change the requirements for the person who can hold the specified position.